Formulation, Evaluation, And Optimization of Coscinium Fenestratum-Based Niosomal In-Situ Gel for Anti-Cataract: Pharmaceutical Science-Pharmaceutics - Menon, Gowtham; C Sutar, Ravindra; CP, Sachin; R S, Shendge; A Kashid, Girish (International Journal of Life Science and Pharma Research, 2023)
Coscinium fenestratum is a sturdy, creeping, woody plant that grows with a cylindrical, yellowish stem that belongs to the family Menispermaceae and is commonly known as tree turmeric. The research aims to develop a niosomal in-situ gel by incorporating a novel drug carrier, such as a niosome containing herbal extract for treating cataracts. The niosomal carrier was prepared by varying concentrations of two surfactants, while the herbal drug and cholesterol concentration was kept constant. The optimization of the niosome was done based on the size and shape of the vesicle obtained from SEM analysis. The optimized niosomal dispersion was then converted to a niosomal in-situ gel, and evaluations were carried out, like pH, viscosity, gelling capacity, gel strength, and isotonicity. From the preliminary phytochemical screenings of Coscinium fenestratum, the ethanolic extract showed the intense presence of flavonoids, alkaloids, steroids, and saponins. The drug-loaded niosomes were stable in HPMC, HPMC K15M, and Carbopol 940 ocular in-situ Gel, and the optimum HLB value of the surfactant span 60 made this formulation more stable. The Brookfield viscometer determined the viscosity, which is an important factor in determining the residence time of the drug in the eye. It possessed good viscosity of about 982.66 ± 1.52 cps. From a gelling capacity study conducted, it was found that the niosomal in-situ Gel possesses immediate gelation and remains for an extended period. The gel strength of niosomal in-situ Gel was 1.30 ± 0.006 sec, and when subjected to isotonicity testing, the results were acceptable. Stability studies were conducted at two different temperatures where no color changes occurred, and there was not much difference in parameters like pH, viscosity, gelling capacity, and gel strength. So it was concluded that the niosomal in-situ Gel of Coscinium fenestratum can be an alternative method to reduce the drawbacks of conventional ophthalmic dosage forms.